Dynamics of customary land disputes and implementation of indigenous peoples' rights: a systematic study in the perspective of indonesian agrarian law - Rian Cantona (Yayasan Cinta Negara, 2025)
Customary land disputes are an agrarian problem that continues to occur in Indonesia due to the unsynchronization between customary law and state law. Although the Basic Agrarian Law (UUPA) and several Constitutional Court decisions have recognized the rights of indigenous peoples to customary land, its implementation still encounters various obstacles. This study aims to analyze the main causal factors of customary land disputes and evaluate the effectiveness of existing regulations and settlement mechanisms. Using a systematic literature review method, this research examines various legal, social, economic and political aspects that influence the dynamics of customary land conflicts in Indonesia. The results show that unsynchronized regulations, weak law enforcement, and investment and development interests are the main factors that trigger conflicts between indigenous peoples, the government, and the private sector. In addition, the lack of legal protection mechanisms for indigenous peoples causes them to often experience evictions and criminalization when defending their customary land rights. The study also highlights more effective dispute resolution models, including strengthening the role of customary institutions, implementing Free, Prior, and Informed Consent (FPIC) mechanisms, and establishing independent institutions to deal fairly with agrarian conflicts